PCR- Based Test for the Early Warning of Both Cylindrospermopsin and Saxitoxin in Iraqi Freshwater - Abed, Ibrahim J (Al-Nahrain Journal of Science, 2018)
Cylindrospermopsins (CYN) and saxitoxins (STXs) are neurotoxins produced by a variety species of cyanobacteria. CYN is recognized as one of the most globally important of the freshwater algal toxins. STXs are mostly associated with marine dinoflagellates (eukaryotes) and several species of freshwater cyanobacteria. The aim of this study was to provide a rapid tool to detect cylindrosprmopsin and saxitoxin biosynthesis genes in freshwater and bloom. Microscopic identification of the studied samples demonstrated that the prevalent cyanobacteria in samples of freshwater and blooms were Lyngbya, Oscillatoria, Aphanizomenon, Chroococcus, Microcystis, Cylindrospermopsis and Anabaena. The molecular analysis revealed that aoaC gene was not detected in the freshwater samples at the three studied sites while sxtA was detected at one only. Also, the aaaC and sxtA genes were detected in the bloom at the three studied sites. In conclusion, The PCR technique applied in this paper was found to be useful and rapid test, particularly when the number of the target organism is very low in the freshwater sample.